2020
DOI: 10.22271/j.ento.2020.v8.i5r.7680
|View full text |Cite
|
Sign up to set email alerts
|

Market profile and consumer purchase pattern of honey in Tamil Nadu

Abstract: Beekeeping is one of the oldest activities in India and makes it into the leading honey market in the world which has created an intense competition in terms of innovation. With the increasing market size and increasing consumer demand each year, honey makers have to search for new approaches and to learn to understand the consumers' need in order to improve their product satisfaction and customers' loyalty. The purpose of this study is to determine the purchase pattern of honey by the consumers in Tamil Nadu.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Mateescu et al [72] state that a flavoured creamed honey is a good choice for consumers who are interested in consuming a spreadable product with an original flavour and nutritional benefits. Leaka et al [73] found that in addition to plain honey, consumers also prefer health-enriched and flavoured honeys for consumption. It can be concluded that these additions to honey create additional value compared to the original value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mateescu et al [72] state that a flavoured creamed honey is a good choice for consumers who are interested in consuming a spreadable product with an original flavour and nutritional benefits. Leaka et al [73] found that in addition to plain honey, consumers also prefer health-enriched and flavoured honeys for consumption. It can be concluded that these additions to honey create additional value compared to the original value.…”
Section: Discussionmentioning
confidence: 99%
“…Consumers of the Baby Boomers Generation tend to consume honey with ginger and honey with nuts. Furthermore, Leaka et al [73] emphasise that consumers prefer honey with the addition of dried fruit or flavoured honeys, such as lemon or cinnamon. However, other honeys are also available on the market, e.g., Eucalyptus honey, Jamun honey and Tulsi honey.…”
Section: Discussionmentioning
confidence: 99%
“…Honey with other additions such as chocolate or fruits can be interesting for children's consumers as a suitable alternative to sweet spreads or jams (Šedík et al, 2023a;Šedík et al, 2020;Miłek et al, 2021;Habryka et al, 2020;Sowa et al, 2019, Guldas et al, 2022. Leaka et al, (2020) found that the mentioned type of honey is consumed by consumers. Flavoured creamed honey can be a suitable alternative for consumers who like a spreadable product with an original taste and nutritionnal/functional benefits (Mateescu et al, 2020).…”
Section: Fig 1 Preferred Ingredients For Flavoured Honeymentioning
confidence: 99%
“…Honey with other additions such as chocolate or fruits can be interesting for children's consumers as a suitable alternative to sweet spreads or jams (Šedík et al, 2023a;Šedík et al, 2020;Miłek et al, 2021;Habryka et al, 2020;Sowa et al, 2019, Guldas et al, 2022. Leaka et al, (2020) found that the mentioned type of honey is consumed by consumers. Flavoured creamed honey can be a suitable alternative for consumers who like a spreadable product with an original taste and nutritionnal/functional benefits (Mateescu et al, 2020).…”
Section: Fig 1 Preferred Ingredients For Flavoured Honeymentioning
confidence: 99%